Controlled crystallization of anhydrous guanine β nano-platelets via an amorphous precursor. Issue 23 (23rd May 2019) - Chen, Fenghua; Wu, Bianbian; Elad, Nadav; Gal, Assaf; Liu, Yanan; Ma, Yurong; Qi, Limin
Abstract : We realized a pure phase of anhydrous guanine (AG) β form for the first time via a transformation from hydrated amorphous guanine phase (HAmG). The specified transformation was probably due to the similar short-range order between AG β and HAmG. Abstract : As important optical devices, including diffuse scatterers, broadband reflectors, and image-forming mirrors with superior properties, biological guanine crystals have been thoroughly investigated in recent years. However, controlling the polymorph and morphology of synthetic guanine crystals is still highly challenging. Herein, a pure phase of the anhydrous guanine (AG) β form was obtained via transformation of a hydrated amorphous guanine phase (HAmG) in solvents such as formamide, DMSO and DMF. The AG β crystals can be stable for up to three months in the above solvents. The AG β nano-platelets obtained in DMSO exposed the (100) plane when polyvinylpyrrolidone (PVP) was applied as an additive. The AG β nano-platelets were about 100 nm in length, 40 nm in width, and 10–20 nm in thickness. Solid-state NMR (ssNMR) characterization indicated that the HAmG precursor had a similar short-range order as AG β, which might be the reason for the formation of AG β instead of the thermodynamically more stable AG α. The delicate control of the polymorph and morphology of the guanine crystals via an amorphous phase strategy may inspire the formation of highly ordered hierarchical structures of guanine crystals with unique optical properties.